1990
DOI: 10.1111/j.1538-4632.1990.tb00212.x
|View full text |Cite
|
Sign up to set email alerts
|

Requiem for the Net Migrant

Abstract: Scores of papers published over the past two decades have reported on efforts to identify the determinants and project the consequences of interregional migration within various nations. Generally, such studies have sought to associate data on migration streams between pairs of regions and such variables as wage rates, unemployment rates, income levels, education, degrees of urbanization, and the distances separating origin and destination regions. Among the several ways of adjusting for relative differences i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
83
0
3

Year Published

1999
1999
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(87 citation statements)
references
References 22 publications
(11 reference statements)
1
83
0
3
Order By: Relevance
“…Third, estimates of bilateral ows provide a far greater depth to the understanding of international migration than can be obtained from net migration measures. As Rogers (1990) details, net migration statistics are fundamentally awed as they are based on a non-existent population. Further, they are sensitive to changes in both immigration or emigration patterns and hence their time series are often volatile.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, estimates of bilateral ows provide a far greater depth to the understanding of international migration than can be obtained from net migration measures. As Rogers (1990) details, net migration statistics are fundamentally awed as they are based on a non-existent population. Further, they are sensitive to changes in both immigration or emigration patterns and hence their time series are often volatile.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Until recently net migration ow estimates produced every two years by the United Nations have served as the sole comprehensive source of global migration ow data. However, as with any net measure, they are susceptible to distorting and disguising the underlying patterns (Rogers, 1990) and hence are of limited explanatory use. More detailed measures, such as the immigration and emigration counts into each country, or country to country bilateral ows are far better equipped to explain and predict global migration trends.…”
Section: Introductionmentioning
confidence: 99%
“…A location with a large ratio (positive or negative) is an important node in the redistribution of the population -absorbing population when the ratio is positive, shedding population when it is negative. Effectiveness allows the analyst to compare migration loss and gain across states and groups of different sizes -something net migration cannot (Rogers 1990;Stillwell et al 2000). Identifying "migration effective" locations for different groups and arrival cohorts through time illuminates the roles of different places in the mobility system of migrants.…”
Section: The Channelization Of Migration: Migration Fields and Networmentioning
confidence: 99%
“…Averaging over three years gives a better idea of longer-term trends, and helps remedy the problem of exceptionally lowhigh oneyear flows. Recent studies have cited problems with net migration measures (Rogers, 1990), and suggested an alternative-demographic effectiveness (Plane and Rogerson 1994). However, to maintain comparability with Beale's previous work, net migration measures were used.…”
Section: Variations In Net and Gross Migration Ratesmentioning
confidence: 99%